FDZ data description: Regional real estate price indices for Germany (RWI-GEO-REDX) - Larissa Klick; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
[Introduction] An important issue in the current German public and political discourse is the development of housing prices. Sharply increasing rents, shortage of living space in urban areas and rural exodus are some of the discussed problems. Despite its topicality, few data are available on the recent development of housing prices in Germany. To fill this gap, the RWI-GEO-REDX data set quantifies regional differences in house purchase and apartment rent prices on the level of districts (Kreise, NUTS 3-level) and municipalities (Gemeindeverband, LAU 1-level). [...]
Keywords: 330